“I Still Need Your Help”: Online information seeking behavior of International Students in the United States on Reddit - Sangpil Youm; Chaeeun Han; Hojeong Yoo; Sou Hyun Jang; Bonnie J. Dorr (PLoS ONE, 2026)
This study examines the online information-seeking behavior of international students in the United States. Following the onset of COVID-19, their need for timely and relevant information becomes critical. Despite greater challenges than domestic students, limited research explores how international students use online platforms to meet their unique information needs. With online communities being essential sources of information and bridges for online social capital, our study analyzes the r/f1visa subreddit to examine international students’ information-seeking patterns before and during the COVID-19 pandemic. Additionally, we identify unmet information needs through members’ interactions and recurring questions. Our analysis reveals a shift in topics, with pandemic discussions focusing on travel, financial difficulties, and entry concerns, while pre-pandemic conversations primarily about employment. The increased similarity among recurring questions during the pandemic suggests a convergence of shared struggles that fosters solidarity and emotional support, even as many informational needs remain inadequately addressed. By examining international students’ information needs through the theoretical lens of online social capital, this study contributes to understanding how crisis conditions reshape the dynamics of online communities, blurring traditional distinctions between bonding and bridging capital. The findings can inform universities, policymakers, and online community designers in developing more responsive and inclusive information environments that recognize both the instrumental and emotional support functions of digital platforms for international students.